L’intégration professionnelle de médecins diplômés à l’étranger au Québec : un enjeu d’envergure en santé mondiale - Marie-Jeanne Blain; José Carlos Suárez-Herrera; Sylvie Fortin (Anthropologie & Santé)
In a context where the processes of production and transfer of technical expertise are nested in a logic of global markets, current health care systems have to face many challenges related to the international mobility of health professionals. Inspired by theoretical approaches of anthropology of health and the sociology of organizations, we discuss the complex dynamics between global phenomena associated to the globalization of contemporary societies and local issues concerning the international mobility of health professionals and, in this specific case, the integration of international medical graduates in Quebec’s labor market. In this perspective, a socio-anthropological approach to Global Health sheds light on the interplay between local power strategies and global social inequalities.